Indo-European and Indo-Europeans : Papers Presented at the Third Indo-European Conference at the University of Pennsylvania - Cardona, George; Hoenigswald, Henry M.; Senn, Alfred (Haney Foundation Series, 2016)
Twenty-two internationally known linguists, anthropologists, and archaeologists discuss such questions as the original home of the Indo-Europeans, their migration, religiomythic beliefs, and legal customs in the most comprehensive treatment of Indo-European culture in recent times.